Is active travel associated with greater physical activity? The contribution of commuting and non-commuting active travel to total physical activity in adults() - Sahlqvist, Shannon (Academic Press, 2012)
BACKGROUND: To complement findings that active travel reduces the risk of morbidity and mortality from chronic diseases, an understanding of the mechanisms through which active travel may lead to improved health is required. PURPOSE: The aim of this study is to examine the descriptive epidemiology of all active travel and its associations with recreational and total physical activity in a sample of adults in the UK. METHODS: In April 2010, data were collected from 3516 adults as part of the baseline survey for the iConnect study in the UK. Travel and recreational physical activity were assessed using detailed seven-day recall instruments. Linear regression analyses, controlling for demographic characteristics, examined associations between active travel, defined as any walking and cycling for transport, and recreational and total physical activity. RESULTS: 65% of respondents (mean age 50.5 years) reported some form of active travel, accumulating an average of 195 min/week (standard deviation = 188.6). There were no differences in the recreational physical activity levels of respondents by travel mode category. Adults who used active travel did however report significantly higher total physical activity than those who did not. CONCLUSIONS: Substantial physical activity can be accumulated through active travel which also contributes to greater total physical activity.